Clinical misconceptions and diagnostic delays in extrapulmonary tuberculosis: an evaluation on 89 cases - Emel Gürcüoglu (Journal of Infection in Developing Countries)
Introduction: Extrapulmonary tuberculosis (EPTB) has highly variable clinical findings, and has a more difficult diagnostic process than pulmonary tuberculosis (PTB). The aim of this study was to examine the difficulty of the diagnostic process in 89 cases that applied to different clinics in our hospital, with different complaints.